Absence of short-term changes in knowledge and attitudes among household contacts of COVID-19 cases during the post-acute phase of the pandemic in Catalonia and Navarre, Spain - Vanessa Bullón-Vela; Vanessa Bullón-Vela; Diana Toledo; Diana Toledo; Aitziber Echeverría; Pere Godoy; Pere Godoy; Pere Godoy; Manuel García Cenoz; Manuel García Cenoz; Manuel García Cenoz; Ignasi Parrón; et al. (Frontiers Media S.A., 2024)
ObjectivesTo evaluate short-term changes in knowledge and attitude towards COVID-19 and preventive measures during the post-acute phase of the pandemic in Spain.MethodsA survey was performed in Catalonia and Navarre between May-2022 and July-2023 in household contacts of COVID-19 cases. Knowledge and attitude were assessed at baseline and at three months, using a Likert scale. Responses were grouped according to correct or incorrect.ResultsAt baseline, 172 subjects were contacted, 118 (69%) of which completed a follow-up interview three months later. Knowledge of correct hand-washing and mask protocols had maintained over time (−1.7%, p = 0.553 and − 2.5%, p = 0.473, respectively). Attitudes toward preventive measures was adequate in the first interview (86%), but attitudes regarding use of face masks decreased significantly (−9.1%, p = 0.048) over time in participants with higher risk of severe COVID-19. However, most short-term changes in knowledge and attitudes were not statistically significant.ConclusionHousehold contacts showed correct knowledge and attitude towards COVID-19 and its preventive measures, without significant changes in the short term despite a relaxation of government-mandated preventive measures. These results provide relevant information in case of a new health emergency due to respiratory viruses.